Fetal ultrasound scans to guide management of gestational diabetes: Improved neonatal outcomes in routine clinical practice. (March 2021) - Davidson, Sarah J.; de Jersey, Susan J.; Britten, Fiona L.; Wolski, Penny; Sekar, Renuka; Callaway, Leonie K.
Abstract: Aims: Some guidelines recommend altering glycemic targets in gestational diabetes mellitus (GDM) based on ultrasound measurements of fetal growth, but the impact on outcomes in clinical practice is unknown. The aim of this study was to compare the effects of ultrasound-guided and non-ultrasound-guided management on neonatal outcomes. Methods: This was a retrospective, observational study of a random sample of women with GDM and their infants. Outcomes were compared between those who had GDM management tailored according to fetal growth and those who did not. Results: In the sample of 221 women, 134 had documentation of ultrasound-guided management while 87 did not. There was no significant difference in size-for-gestational age between groups. Fewer neonates in the ultrasound-guided management group were admitted to the Special Care or Intensive Care Nursery (29.1% vs. 48.3%, P = 0.004), had a prolonged hospital stay (3.7% vs. 13.8%, P = 0.006), or had hypoglycemia after birth (42.5% vs. 56.3%, P = 0.045). The reduction in admission rates and prolonged hospital stays remained significant after controlling for confounding variables. Conclusions: Ultrasound-guided management was independently associated with improvements in some neonatal outcomes.